STUDI REKRUITMEN DAN PENGEMBANGAN PROFESI KEPALA SEKOLAH SEBAGAI PIMPINAN SATUAN PENDIDIKAN DI KECAMATAN SELUPU REJANG - Sumarno Sumarno (UNIVERSITAS BENGKULU, 2015)
The purpose of this research is to describe the recruitment process and proffessional development of principals as leader of education unit. Research method use descriptive research with subject are 15 principals of elementary school in Selupu Rejang. Data collection technique through interviews and documentation. Data analysis using codification and data reduction, data analysis, inference and verification. General conclusion that the principals recruitment process in Selupu Rejang has not referring to Permendiknas number 13 of 2007.Keyword: recruitment, proffessional development of principals